How does working memory affect learning? The interrelationship among working memory, language learning, and mathematical achievement - Okay, Aysegul; Cedden, Gulay (TAYLOR & FRANCIS LTD, 2025)
This study investigates the relationship among working memory (WM), mathematics, and language, with the aim of understanding: (1) whether the functions and capacities of WM components can predict achievement in language and mathematics; and (2) whether competence in the first language (L1) and achievement in mathematics can predict success in later second language (L2) learning. The participants were 60 Turkish-English bilingual young adults. Data were collected through the Digit Span Task, standardized exams, and a computerized Turkish Reading Span Task developed for this study. The results reveal that: (1) WM significantly explains achievement in both language and mathematics, and (2) competence in L1 and mathematics predicts success in later L2 learning. Based on these findings, it is hypothesized that the domain-specific abilities of language and mathematical skills might share a core network that is strongly linked to the mechanisms of the phonological loop and the central executive, and that rehearsal techniques may modulate the learning achievement of languages and mathematics.
Keywords: Working memory; mathematics; language; Digit Span Task; Reading Span Task; READING SPAN TEST; INDIVIDUAL-DIFFERENCES; PHONOLOGICAL MEMORY; CAPACITY; COMPREHENSION; CHILDREN; COMPONENTS; ATTENTION; LITERACY; DEFICITS; Education & Educational Research; Psychology